EQUIPPING PHARMACISTS AND OTHER HEALTH PROFESSIONALS FOR THE ADVENT OF PERSONALIZED MEDICINE AND HIGH-THROUGHPUT PHARMACOGENOMICS. - NILOFAR DANESHI; MYFANWY GRAHAM; ELIZABETH MILWARD (International Journal of Pharma and Bio Sciences, 2015)
New high-throughput approaches to pharmacogenomics are now enabling multiple gene variants to be screened simultaneously and cost effectively in large numbers of people. This is rapidly changing the face of modern healthcare. For this field To reach its full potential, healthcare professionals will need to undertake high-level continuing education programs that build their understanding of these fast evolving advances in pharmacogenomics and the applications of new technologies in personalized medicine.